Does investment in education and health impact youth employment outcomes? Evidence from Sub-Saharan Africa - Oluchukwu F. Anowor; Hyacinth E. Ichoku; Vincent A. Onodugo; Chinedu Ochinanwata; Peter Chika Uzomba (Cogent Economics & Finance, 2023)
Labour engagement, underutilization and unemployment has dominated discourse in development literature in developing economies. It tangentially dictates the direction of migration, gross domestic output and in some cases, youth restiveness. This study investigated the unique relationship between investment in human capital proxied by spending in education and health and its effects on youth employment outcomes in Sub-Saharan Africa (SSA). Annual data spanning 1995-2017 were obtained from 40 SSA countries comprising 920 macro panel observations. The bootstrap-based bias correction for the panel fixed effects estimation technique was employed to improve on the analytical corrections. Findings suggest that human capital investment comprising private and government health expenditures, primary, secondary and tertiary education expenditures were found to have varying significant impact on youth employment in SSA. The policy implication is that to reverse the perennial problem of youth unemployment in SSA would require serial consistent disproportionate investment more in education than in health.
Keywords: H51; H52; I15; I18; I22; J01; J08; J24; 330; education; expenditures; health; Human capital; Sub-Saharan Africa; youth employment